Analysis of Service Quality Factors in the Grab Application on User Satisfaction using the Service Quality (SERVQUAL) Method - Yanto, Dimas Hadi; Indah, Dwi Rosa; Novianti, Hardini; Sanjaya, M. Rudi; Gumay, Naretha Kawadha Pasemah (Sistemasi: Jurnal Sistem Informasi, 2025)
The development of information technology in the digital era has had a significant impact, including on online transportation services such as Grab. However, Grab users frequently complain about slow response times from customer support when handling complaints, as well as recurring issues with the balance feature, as reflected in complaints like "saldo" (balance) and "please fix this". This study aims to identify the factors influencing the service quality of the Grab application on user satisfaction in Palembang using the Service Quality (SERVQUAL) approach. A quantitative research method was employed, involving 106 respondents who are Grab users. Data were collected through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to measure the impact of five SERVQUAL dimensions: responsiveness, reliability, tangibles, empathy, and assurance. The findings indicate that these five dimensions collectively have a highly significant effect on service quality (F = 41.92). Individually, the tangibles dimension has the most dominant impact (t = 4.473, p < 0.05), followed by empathy, which also shows a significant influence (t = 2.248, p < 0.05). However, reliability, responsiveness, and assurance do not exhibit significant effects. These results highlight the need for service quality improvements, particularly in the dimensions that were found to be less significant, to enhance the Grab application’s user experience in Palembang.